Recovery of coffee cultivars under the ‘skeleton cut’ pruning after 4.5 years of age - Silva, Vania Aparecida; Rezende, Juliana Costa de; Carvalho, Alex Menndonça de; Carvalho, Gladyston Rodrigues; Rezende, Tiago Teruel; Ferreira, Andre Dominghett (Coffee Science - ISSN 1984-3909, 2016)
In view of the adverse weather in the last years as well as the intensification of pruning in new crops, it evaluated the vegetative and reproductive resilience after pruning type ‘skeleton cut’ in 24 commercial cultivars of C. arabica crop in 4.5 years of age. At 24 months after the pruning, the agronomic characteristics were evaluated by yield, floating grains percentage, bean size and vegetative vigor of the plants. The yield data were evaluated by analysis of deviance in double factorial 24x2, 24 cultivars and two types of conduction (submitted or not to pruning). Using the average of the three years and the other agronomic traits (mentioned above) were evaluated in factorial triple 24x2x2, 24 cultivars, two types of conduction (with pruning and no pruning) and two years of evaluation (harvests 2012/2013 and 2013/2014). In all studied traits, there was no overlap of confidence intervals, indicating that the cultivars had different performance each other. All the cultivars had resilience after pruning type ‘skeleton cut’ in young stage, especially the cultivars Catiguá MG3, Topazio MG1190 and Sabia 398 that showed high productivity combined with a vegetative vigor, low floating grains percentage and good percentage of grains sieve high in the first two years after pruning.